The Influence of Parenting Styles on the Independence of 5–6 Year Old Children in Dressing - Irwansyah, Asep; Puspitasari, Putri Ratih; Sopiah; Deswita, Dea (LPPM Universitas Mohammad Husni Thamrin, 2025)
Early childhood is in its golden age, a crucial period for physical, cognitive, social, and emotional development. During this period, children are highly sensitive to stimulation from their environment, particularly the family, their primary and primary environment. Children’s independence is an essential aspect of early childhood development that should be stimulated from an early age, particularly in self-help skills such as dressing. Parents play a crucial role through the parenting styles they apply. This study aims to determine the influence of parental parenting styles on the independence of children aged 5–6 years in dressing. This research employed a quantitative approach with a correlational survey method. The sample consisted of 35 children aged 5–6 years at Aisyiyah Bustanul Athfal 91 Kindergarten, Rawalumbu, selected using a census sampling technique. Data were collected using validated and reliable questionnaires on parenting styles and children’s dressing independence. Data analysis was conducted using simple linear regression. The results showed that parental parenting styles had a positive and significant effect on children’s independence in dressing, with a regression coefficient of 0.147, a t-value of 2.966 greater than the t-table value of 2.034, and a significance value of 0.006 < 0.05. Thus, it can be concluded that better parental parenting styles contribute to higher levels of independence in dressing among children aged 5–6 years.